Desktop system for accounting, audit, and research in A&E. Issue 2 (March 1997) - Taylor, C J; Brain, S G; Bull, F; Crosby, A C; Ferguson, D G
Abstract : The development of a database for audit, research, and accounting in accident and emergency (A&E) is described. The system uses a desktop computer, an optical scanner, sophisticated optical mark reader software, and workload management data. The system is highly flexible, easy to use, and at a cost of around 16, 000 pounds affordable for larger departments wishing to move towards accounting. For smaller departments, it may be an alternative to full computerisation.